Servicescape factors affecting level of customer satisfaction toward Melaka Sentral Sdn Bhd (MSSB) / Aini Tasnim Mohamad - Mohamad, Aini Tasnim (Faculty of Business and Management, 2008)
The intensely competitive environment makes it vital for the firms achieve customer satisfaction in order to survive in the long term. This research study review on "Servicescape Factors Affecting Level of Customer Satisfaction toward Melaka Sentral Sdn Bhd (MSSB)". The purpose of this study is to know level of cutomer satisfaction.